2018
DOI: 10.3390/ma11112068
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Aggregation in Thin Films of Polymer Blends for Solar Cell Applications

Abstract: We report on the effects of the film morphology on the fluorescence spectra for a thin film including a quinoxaline-based co-polymer (TQ1) and a fullerene derivative ([6,6]-phenyl-C71-butyric acid methyl ester—PC70BM). The ratio between the polymer and the fullerene derivative, as well as the processing solvent, were varied. Besides the main emission peak at 700 nm in the fluorescence spectra of thin films of this phase-separated blend, a broad emission band is observed with a maximum at 520–550 nm. The intens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In a number of pure and mixed organic solvents, fullerene С n (n = 60, 70, 76, …) molecules show a pronounced tendency to self-assembly and the formation of fairly large functional fullerene aggregates of various shapes and sizes. The problem was fundamentally studied by different physical and chemical methods in [3][4][5][6][7][8][9][10][11] and the obtained results provided a vector toward potential applications in material chemistry [12,13], biomedicine [14][15][16], phototherapy [17][18][19], molecular electronics [20], optoelectronics [21,22] and solar energy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In a number of pure and mixed organic solvents, fullerene С n (n = 60, 70, 76, …) molecules show a pronounced tendency to self-assembly and the formation of fairly large functional fullerene aggregates of various shapes and sizes. The problem was fundamentally studied by different physical and chemical methods in [3][4][5][6][7][8][9][10][11] and the obtained results provided a vector toward potential applications in material chemistry [12,13], biomedicine [14][15][16], phototherapy [17][18][19], molecular electronics [20], optoelectronics [21,22] and solar energy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…An advance in the field of organic solar cells (OSCs) is of increasing interest, both from a fundamental and an applied point of view, as OSCs offer broad opportunities to produce electricity in a sustainable way as well as showing multiple technical benefits, e.g., solution processability, flexibility, and light-weight [1,2,3,4,5,6]. The commercialization of OSC technology will depend on three key factors: Device efficiency, lifetime, and cost [7].…”
Section: Introductionmentioning
confidence: 99%
“…This field has gained much attention as it promises low-cost, flexible, and aesthetically pleasing solar energy harvesting devices. [1][2][3][4][5][6] Solution processability of materials allows, for example, the possibility to use roll-to-roll printing adapted from the printing industry for the large-scale production of organic solar cells. 7 OSCs are multilayered semiconducting devices, 8,9 consisting of a photoactive layer between two electrodes.…”
mentioning
confidence: 99%
“…We have shown that the equipment can be used to prepare thin films of polymer blends from solution in a safe and reliable way under microgravity conditions. We used a well-studied model system 1,14,[24][25][26] The results presented here show that the custom-designed equipment works as intended and that the dip-coated films can be produced under microgravity conditions. This also shows the possibility to transfer OSC production from Earth conditions to space conditions, a research field that presently is at an early stage with, to our knowledge, only two reports on exploring the use of OSCs in space applications.…”
mentioning
confidence: 99%